Investigation of In Vitro Effects of Daptomycin, Tigecycline and Teicoplanin Combinations against MRSA, VISA and VRE Strains - Coban, Ahmet Yilmaz; Deveci, Aydin; Acicbe, Ozlem; Fisgin, Nuriye Tasdelen; Ciftci, Alper; Dokuzoguz, Basak; Durupinar, Belma (Academic Journals, 2010)
Multidrug resistant (MDR) gram positive infectious agents can cause severe infections and monotherapy of these infections by current available antimicrobial agents can be problematic. Therefore, antimicrobial combination therapy may be needed for effective treatment. The study aimed to investigate in vitro effects of binary combinations of tigecycline (TGC), daptomycin (DPC) and teicoplanin (TP) against 4 methicillin resistant Staphylococcus aureus (MRSA), 2 vancomycin intermediate S. aureus (VISA) and 9 vancomycin resistant enterococci (VRE) species by E test method. Whilst, all binary combination of TGC, DPC and TP showed synergistic effect against standard strain of S. aureus and 50% of clinical MRSA isolates, all of the combinations except DPC-TP combination showed additive effect against VISA strains (Mu 3 and Mu 50). TGC-TP, DPC-TP and TGC-DPC combinations showed additive effect against 25, 60 and 50% of clinical VRE isolates, respectively. Synergistic effect was observed in combinations of TGC-TP and DPC-TGC against 2 and 1 VRE clinical isolates, respectively. Combinations of TP with any of TGC and DPC brought MIC values of TP below the level of sensitivity in all of TP resistant VRE and VISA isolates. Antagonistic effect was not observed in combinations of tested drugs against any strains. In conclusion, in vitro effectiveness of these drug combinations may reflect advantages in clinical practice for severe MDR gram positive bacterial infections.
Keywords: Multidrug Resistant; Antimicrobial Agents; Methicillin Resistant Staphylococcus Aureus; Infectious Agents; Vancomycin Resistant Enterococci